Higher vs lower doses of dexamethasone in patients with COVID‐19 and severe hypoxia (COVID STEROID 2) trial: Protocol and statistical analysis plan. Issue 6 (9th March 2021) - Munch, MW; Granholm, Anders; Myatra, SN; Vijayaraghavan, BKT; Cronhjort, Maria; Wahlin, RR; Jakob, Stephan M.; Cioccari, Luca; Kjær, MN; Vesterlund, GK; Meyhoff, TS; Helleberg, Marie; et al.
Abstract : Background: The coronavirus disease 2019 (COVID‐19) pandemic has resulted in millions of deaths and overburdened healthcare systems worldwide. Systemic low‐dose corticosteroids have proven clinical benefit in patients with severe COVID‐19. Higher doses of corticosteroids are used in other inflammatory lung diseases and may offer additional clinical benefits in COVID‐19. At present, the balance between benefits and harms of higher vs. lower doses of corticosteroids for patients with COVID‐19 is unclear. Methods: The COVID STEROID 2 trial is an investigator‐initiated, international, parallel‐grouped, blinded, centrally randomised and stratified clinical trial assessing higher (12 mg) vs. lower (6 mg) doses of dexamethasone for adults with COVID‐19 and severe hypoxia. We plan to enrol 1, 000 patients in Denmark, Sweden, Switzerland and India. The primary outcome is days alive without life support (invasive mechanical ventilation, circulatory support or renal replacement therapy) at day 28. Secondary outcomes include serious adverse reactions at day 28; all‐cause mortality at day 28, 90 and 180; days alive without life support at day 90; days alive and out of hospital at day 90; and health‐related quality of life at day 180. The primary outcome will be analysed using the Kryger Jensen and Lange test adjusted for stratification variables and reported as adjusted mean differences and median differences. The full statistical analysis plan is outlined in this protocol. Discussion: The COVID STEROID 2 trial will provide evidence on the optimal dosing of systemic corticosteroids for COVID‐19 patients with severe hypoxia with important implications for patients, their relatives and society.